Adverse childhood experiences and intimate partner violence in adulthood among transgender women: exploring the chain mediating role of self-esteem and LGBT minority stress - Lulu Xu; Huifang Xu; Zuxin Wang; Jiani Hu; Yawen Zheng; Fengyi Wang; Ruijie Chang; Ying Wang; Yong Cai (Annals of Medicine)
Background Transgender women experience a high incidence of intimate partner violence (IPV) in adulthood. The well-documented risk factors contributing to IPV include adverse childhood experiences (ACEs), low self-esteem, and the minority stress experienced by LGBT individuals. The object of the present study was to examine how ACEs influence IPV in adulthood, and to explore the chain mediating function of self-esteem and LGBT minority stress.Methods In February 2022, we recruited 264 transgender women through snowball sampling in Shenyang, China. Participants completed a questionnaire assessing background characteristics, ACEs, IPV in adulthood, self‐esteem and LGBT minority stress. Relationships among study variables were examined through variance and correlation analyses. A chain mediation model was tested using PROCESS.Results There was a significant correlation among the four variables. ACEs positively predicted IPV in adulthood (r = 0.449, p < 0.001). The sequential mediation model demonstrated that self-esteem (the estimated effect = 0.0708, 95%CI: 0.0152–0.1327) and minority stress (the estimated effect = 0.0404, 95%CI: 0016–0.0847) had the potential to mediate the connection between ACEs and IPV respectively. Additionally, the combined mediating influence of self-esteem and minority stress (the estimated effect = 0.0298, 95%CI: 0.0105–0.0591) similarly exerted such an effect. In summary, the mediating effect accounts for 34.59% of the overall effect size.Conclusion Taken together, the findings underscore the high prevalence of IPV among Chinese transgender women, highlighting the need for additional attention from violence service providers and other healthcare professionals on ACEs, low self-esteem, and minority stress, as these factors may place this population at risk for IPV.